More than a century old ‘Platycleis Kraussi case’ finally resolved (Tettigoniidae: Platycleidini) - Skejo, Josip; Rebrina, Fran; Tvrtković, Nikola; Gomboc, Stanislav; Heller, Klaus-Gerhard (Zootaxa, 2015)
In this paper we deal with a not well known orthopteran species described from Croatia—Krauss’ bush-cricket, Platycleis kraussi Padewieth, 1900 with unknown type series. After systematic field studies the species was found only three kilometres from Padewieth’s locus typicus, in Francikovac near Senj (Croatia). It was found to be the same as Bicolorana kuntzeni (Ramme, 1931), thus B. kuntzeni (Ramme, 1931) syn. nov. became a synonym of Bicolorana kraussi (Padewieth, 1900) comb. nov. which is moved into genus Bicolorana Zeuner, 1941. Since the type was lost a neotype of B. kraussi is designated and deposited in the Naturalis Biodiversity Center (Leiden, the Netherlands). Historical review of this species’ taxonomy is given. An improved description is presented showing some variability of certain morphological characters. The morphology, morphometrics and bioacoustic data of the species are compared with those of the closely related B. bicolor (Philippi, 1830) and Modestana modesta (Fieber, 1853). Vichetia helleri syn. nov. is regarded a synonym of Bicolorana bicolor. The literature and new distribution data are gathered and presented.